Experiences of migrant mothers attending vaccination services at primary healthcare facilities - Stephan Acheampong; Mygirl P. Lowane; Lucy Fernandes (AOSIS, 2023)
Background: Migration to South Africa is currently dominated by women and children, for socio-economic and refugee reasons or to utilise the healthcare system for various services. Migrants and refugees are at risk of vaccine-preventable diseases, and many of their children have an incomplete or unknown immunisation status. Aim: This study aimed to explore the experiences of migrant mothers in utilising child immunisation services in primary healthcare facilities. Setting: Ten primary healthcare facilities that were providing immunisation services, located in the Buffalo City Metropolitan Municipality, Eastern Cape province, South Africa. Methods: A qualitative research design, making use of in-depth interviews (IDIs) from 18 purposefully selected migrant women, was used for data collection. Thematic content analysis was used to analyse the recorded data of the experiences of study participants in their access to immunisation services. Results: From the IDIs, four themes were identified: difficulty in communicating with the healthcare workers because of language barriers, access challenges, interpersonal barriers and interpersonal relationships were identified in this study, which influenced the utilisation of immunisation services by migrant mothers. Conclusion: The findings of this study support and reinforce the duty of the South African government and healthcare facilities to work together to improve migrant women's access to immunisation services. Contribution: A positive relationship between healthcare workers and migrant mothers while accessing immunisation services should contribute to reducing child mortality in South Africa and achieving Sustainable Development Goal 3 by the year 2030.